El crimen organizado transnacional y su incidencia en el tráfico ilegal de vida silvestre en Ecuador - Oleas Domínguez, Carolina Alejandra; Yánez Flores, Naomi Nathaly (2025)
The research entitled “Transnational organized crime and its impact on illegal wildlife trafficking in Ecuador” analyzes the interaction between three branches of law, environmental, criminal, and comparative, as well as the dimension of international instruments with their application in the national legal framework, especially the Constitution of the Republic of Ecuador, the Organic Environmental Code, and the Comprehensive Organic Criminal Code. Its main objective is to determine how and to what extent the presence of organized criminal networks influences the illegal export of wildlife, from a legal and operational perspective, and to compare this internationally. Specifically, it examines the national and international legal relationships of both variables, together with descriptions of their modes of operation and the existing jurisprudential treatment. The methodology adopted was qualitative, of an exploratory descriptive nature, based on a review of doctrine, legislation, jurisprudence, international treaties, and official reports, together with information obtained from semi-structured interviews with professional experts. Among the results, significant progress has been identified, though limited by deficiencies in inter-institutional coordination, technical resources, and the unequal application of sanctions. In the jurisprudential sphere, despite its regulatory recognition, there has been no evidence of a significant increase in the number of related rulings or precedents. Thus, the study demonstrates the complexity of illegal wildlife trafficking in Ecuador, along with transnational organized crime, and it is pertinent to adopt a comprehensive strategy that reinforces criminal prosecution, international cooperation, and institutional training.